Predictors of Arabic mothers’ practices on early childhood caries in Malaysia - S. A., Najla’a; M. Z., Nor Afiah; K., Hayati (Community Health Society Malaysia, 2015)
Background: Early Childhood Caries (ECC) refers to rampant dental caries in pre-school children. It can affect the child both physically and psychologically. Many factors can affect practice of mothers about prevention of (ECC). The aim of this study is to determine the practice on ECC and its associated factors of Arabic mothers of preschool and primary school children in Arabic schools that are registered in the Ministry of Education Malaysia in Selangor and Wilayah Persekutuan. Materials and Methods: A cross sectional study conducted among 518 mothers of primary and preschool children of all Background: Early Childhood Caries (ECC) refers to rampant dental caries in pre-school children. It can affect the child both physically and psychologically. Many factors can affect practice of mothers about prevention of (ECC). The aim of this study is to determine the practice on ECC and its associated factors of Arabic mothers of preschool and primary school children in Arabic schools that are registered in the Ministry of Education Malaysia in Selangor and Wilayah Persekutuan. Materials and Methods: A cross sectional study conducted among 518 mothers of primary and preschool children of all Arabic schools in Selangor and Wilayah Persekutuan that were registered with the Ministry of Education Malaysia. The respondent was chosen by using simple random sampling. Respondents that fulfilled the inclusion criteria were recruited for the study. Validated and reliable questionnaire assessing on practice of ECC and its factors were used in this study. Chi-square test and binary logistic regression were used for data analysis. Result: The level of good practice on ECC among respondents from this study was 37.8%. The predictors of good practice were respondents with age >35 years old (AOR=4.403; 95% CI: 2.009-9.650), attended infant oral health education program (AOR=2.444; 95% CI: 1.085-5.506), good knowledge level (AOR=1.835; 95% CI: 1.093-3.080), and positive attitude level (AOR=4.605; 95% CI: 2.222-9.541). Conclusion: Majority of mothers’ level of good practice on ECC were poor. Preventive programs related to ECC targeted on the above mothers should be targeted in order to prevent from developing ECC.